Arranjos de milho com Crotalaria spectabilis: produtividade de grãos e comunidade de insetos - Araujo, Ivonete Theodoro (2018)
The maize intercropped with green manures, especially Fabaceae provide in addition to soil protection, nutrient recycling, N deposition through biological fixation and control of spontaneous, also contribute to the increase of natural enemies, playing an important pest control insects. Such benefits of green manures are extremely important for organic corn production. With this work proposed to investigate the effects of Crotalaria spectabilis arrangements in the canopy insect community and corn production components grown in a consortium.The experimental design was a randomized block with five replications. Treatments were corn consortia with C. spectabilis: (CL) - C. spectabilis seeded on the same lines of corn; (EC) - C. spectabilis seeded corn rows; (CLE) - C. spectabilis sown in rows and lines of maize and a control (M) - Single corn. For the community canopy insects evaluated the similarities and major components associated with different arrangements C. spectabilis the consortium as well as the severity of damage caused by H. zea and S. frugiperda in maize. To evaluate the agronomic characteristics of corn evaluated were: plant height (m), ear height, dry weight of the stem (MSC), leaves (SPS) and total (MST), number of rows per ear (NFE), number of kernels per row (NGF), Average grain yield and grain hundred, weight (g) and dry matter of C. spectabilis (MSC). CLE consortium was characterized by the presence of predators and parasitoids, and M is mainly characterized by the presence of, phytophagous chewing f. suckers and also by predators. There was no difference between treatments for the damage caused by S. frugiperda on corn and by H. zea. He graduated two similar groups from the community of insects, f guilds. Chewing / f and parasitoids. sucking/predator. We evaluated the agronomic characteristics, corn production components and also the mass of dry matter production and C. spectabilis consortium. The different arrangements of C. spectabilis not affect the productivity of corn grains which averaged 5 t ha-1. However, LC arrangements of plants and reduced output CLE of dry matter of corn stem. The total dry matter in the consortium was on average 3 t ha-1.